(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the PKA-1 corrosion inhibitor was synthesized based on polyethylenepolyamine and croton aldehyde, its structure was analyzed in YAMR and PMR devices, and its formula was proposed. Also, the inhibition mechanism of this corrosion inhibitor was studied through various thermodynamic parameters. Using the Arrhenius equation, the activation energy (Ea), activation enthalpy (∆H) and activation entropy (∆S) of the steel surface in inhibitory and non-inhibitory environments were determined. Along with this, Langmuir, Frumkin and Temkin adsorption isotherms were studied.